BANK RIAU KEPRI SYARIAH: A REAL STEP TOWARDS SHARIA ECONOMY IN THE MALAY ARCHIPELAGO - Fitri, Mariatul (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
The purpose of this study is to analyze the concrete implementation of Bank Riau Kepri Syariah in promoting the sharia economy in the Malay Archipelago and evaluate its impact on business actors and the local community. The change in status of Bank Riau Kepri to Bank Riau Kepri Syariah marks a significant transformation in the direction of sharia economic development in Riau Province and the Riau Archipelago, known as the Malay land with Islamic civilization. The main problem in this study is how to apply the principles of sharia economics. The research method used is a qualitative descriptive method with a field study approach. The research results show that Bank Riau Kepri Syariah has a significant impact on local economic dynamics. Seventy-eight percent of MSMEs experienced an increase in economic turnover, 70% of respondents acknowledged ease of transactions, and 65% stated that access to business financing has become more open. However, the increase in Islamic financial literacy remains relatively low (48%), and local labor absorption is still suboptimal (58%). This research is expected to serve as a reference for developing Bank Riau Kepri Syariah's future strategy and inspire other regions to develop contextual Islamic-based economic models rooted in local Malay wisdom.